Sol-Gel Chemistry: From Molecule to Functional Materials - Sébastien Clément; Ahmad Mehdi (Molecules, 2020)
Through this Special Issue, you will discover the potentiality of inorganic polymerization (sol-gel process) which is a unique and versatile way for the preparation of materials [...]